9 Evaluation of an alcohol-related brain injury (ARBI) diagnostic service pilot. Issue 8 (20th July 2020) - Jawahar, Kaanthan; Zia Ul Haq Katshu, Mohammad; Ellison, James; Rhinds, David
Abstract : Objectives/Aims: To pilot an ARBI diagnostic service within a community substance misuse team (delivered in partnership with the NHS by a 3rd sector organisation). Background: Alcohol-related brain injury (ARBI) is an umbrella term encompassing alcohol-related cognitive impairment, alcohol-related 'dementias', Wernicke's encephalopathy and Korsakoff's syndrome. It is the result of prolonged and harmful alcohol misuse, developing through direct neuronal damage from alcohol as well as chronic deficient states of vitamin B1 (thiamine). Anecdotally, it is felt that those affected by ARBI can struggle to access the necessary expertise for diagnosis and ongoing management. Methods: A widespread stakeholder engagement process led to the development of a standard operating procedure for the pilot service, utilising a process mapping technique. The service received referrals between September 2018 and January 2019. During this time, assessments were carried out in line with the standard operating procedure by the authors. Referrers were also asked to complete a questionnaire for their views on the service. Results: Referrals were received from several sources within the host third sector organisation. Heterogeneity was seen in presentations and diagnoses made were not limited to ARBI. Referrers spoke highly of the service and how it had positively benefitted their patients going forwards, providing clarity around diagnoses and thus being able to access appropriate support going forwards. There was a clear need demonstrated for such a service. Conclusions: Anecdotally patients with ARBI are viewed as a marginalised group who struggle to access the necessary expertise for diagnosis and ongoing management. This service pilot was successful in filling that gap. Work is ongoing through discussions with local NHS healthcare system partners, including acute trusts, commissioners, mental health, the 3rd sector and Social Care, to devise a more sustainable pathway based upon this pilot service. At present, this is taking the form of an acute hospital 'in-reach' pathway to be trialled in an acute trust. This will provide the basis of a business case for a pathway across the STP footprint.